The multi-tiered medical education system and its influence on the health care market - a China’s flexner report - Hsieh, Chee-Ruey; Tang, Chengxiang (Unpublished, 2019)
Background: Medical education is critical and the first step to foster the competence of a physician. Unlike developed countries, China has been adopting a system of multi tiered medical education to training physicians which is featured by the provision of an alternative lower level of medical practitioners , or known as a feldsher system since 1950s This study aimed to illustrate the impact of multi tiered medical education on both the equity in the delivery of health care services and the efficiency of the health care market. Methods Based on both theoretical reasoning and empirical analysis, this paper documented evidences upon those impacts of the medical education system. Results First, the geographic distribution of physicians in China is not uniform across physicians with different education training. Second, we also find the evidence that high educated doctors are more likely to be hired by larger hospitals, which in turn add the fuel to foster the hospital center health care system in China as pati ents choose large hospitals to chase good doctors. Third, through the channels of adverse selection and moral hazard, the heterogeneity in medical education also imposes costs to the health care market in China. Discussion Overall, the three tiered medical education system in China is a standard policy trade off between quantity and quality in training health care professionals. On one hand, China gains the benefit of increasing supply of health care professionals at lower costs. On the other hand, C hina pays the price for keeping a multi tiered medical education in terms of increasing inequality and efficiency loss in the health care sector. Finally, we discuss the potential policy options for China to mitigate the negative impact of keeping a multi tiered medical education on the performance of health care market.